Overlapping Investigative Authorities of Prosecutors and Police in the Draft Criminal Procedure Code from an Indonesian Constitutional Perspective - Mahmudi, Mohammad; Wildani, Farhan; Jannah, Khairul (JURNAL SULTAN: Riset Hukum Tata Negara, 2025)
The emergence of dualism in investigative authority between the Prosecutor’s Office and the Police in the draft Criminal Procedure Code (RUU KUHAP) has triggered legal ambiguity, resulting in uncertainty within Indonesia’s constitutional system. Investigative authority, which is generally vested in the police as stipulated in the current Criminal Procedure Code (KUHAP), has been expanded—particularly through the provisions of Article 12 paragraph (11) and Article 111 paragraph (2) of the draft law. This situation has the potential to create overlapping jurisdictions, disrupt the principle of due process of law, and weaken the checks and balances within the criminal justice system. The lack of clarity in delineating the boundaries of authority between the police and the prosecutor’s office may lead to institutional conflicts and inefficiencies in law enforcement. This study employs a normative juridical method, utilizing both statutory and conceptual approaches. The statutory approach is used to systematically examine existing and proposed provisions of positive law, while the conceptual approach serves to analyze relevant legal principles and doctrines, including inter-agency coordination within the framework of the rule of law. Therefore, a clear and proportional restructuring of investigative authority is necessary to establish a criminal justice system that is fair, effective, and aligned with the principles of a constitutional state.